Logics in Artificial Intelligence 11th European Conference, JELIA 2008, Dresden, Germany, September 28-October 1, 2008. Proceedings - Hölldobler, Steffen; Lutz, Carsten; Wansing, Heinrich (Lecture Notes in Artificial Intelligence,, 2008)
This book constitutes the refereed proceedings of the 11th European Conference on Logics in Artificial Intelligence, JELIA 2008, held in Dresden, Germany, Liverpool, in September/October 2008. The 32 revised full papers presented together with 2 invited talks were carefully reviewed and selected from 98 submissions. The papers cover a broad range of topics including belief revision, description logics, non-monotonic reasoning, multi-agent systems, probabilistic logic, and temporal logic.